Licensing Disputes in The State Administrative Court System - Regita Dwi Azzahra; Ahmad Ahmad; Putri Aulya Maharani; Syahrul Ardiyansyah Hamid; Siti Athira Hasya; Revalina Keyza; Wahyu Tenggar A Ruby Razzaq Sulaiman; Muhammad Rifadli Rabunah; Rizky Sapta Ramadan Ependi; Endang Mulyadin (Universitas Muhammadiyah Tangerang, 2024)
Licensing is an administrative instrument used by the government to regulate public activities that may generate social, economic, and environmental impacts. In practice, however, the issuance of permits frequently results in disputes due to procedural defects, abuse of authority, and violations of general principles of good governance. This study aims to analyze the characteristics of licensing disputes, the legal framework governing judicial review, and the effectiveness of the Administrative Court in providing legal protection to citizens. The research applies a normative juridical method using statutory and conceptual approaches through the examination of administrative law doctrine and court decisions. The findings indicate that most licensing disputes originate from weak administrative verification, improper use of discretion, and non-compliance with the principles of legality and legal certainty. The Administrative Court functions as a supervisory mechanism by reviewing the legality of administrative decisions and restoring the rights of affected parties. Nevertheless, its effectiveness remains limited due to technical evidentiary difficulties and weak enforcement of judicial decisions by administrative authorities. Therefore, strengthening administrative oversight mechanisms and ensuring execution of court judgments are necessary to establish accountable governance